2013
DOI: 10.1002/btpr.1782
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of mesenchymal stem cells under atmospheric carbon dioxide

Abstract: Stem cells are needed for an increasing number of scientific applications, including both fundamental research and clinical disease treatment. To meet this rising demand, improved expansion methods to generate high quantities of high quality stem cells must be developed. Unfortunately, the bicarbonate buffering system – which relies upon an elevated CO2 environment – typically used to maintain pH in stem cell cultures introduces several unnecessary limitations in bioreactor systems. In addition to artificially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
(213 reference statements)
0
1
0
Order By: Relevance
“…For example, it has been reported that MSCs were able to be expanded up to 22 passages without losing stemness (Estrada et al, 2012;Pierantozzi et al, 2010). Expansion of MSCs under atmospheric CO 2 conditions has been noted to avoid the effects of the bicarbonate buffering system (Brodsky et al, 2013).…”
Section: Addressing the Paradoxes Of Expansionmentioning
confidence: 99%
“…For example, it has been reported that MSCs were able to be expanded up to 22 passages without losing stemness (Estrada et al, 2012;Pierantozzi et al, 2010). Expansion of MSCs under atmospheric CO 2 conditions has been noted to avoid the effects of the bicarbonate buffering system (Brodsky et al, 2013).…”
Section: Addressing the Paradoxes Of Expansionmentioning
confidence: 99%